Peran Otoritas Jasa Keuangan dalam Pengaturan dan Pengawasan Jasa Layanan Keuangan Berbasis Teknologi (Financial Technology) - Femmy Silaswaty Faried; Nourma Dewi (Universitas Islam Balitar, Blitar, 2020)
Technology-based financial services or known as financial technology or abbreviated to fintech is an innovation in the field of financial services. Fintech is in demand and is marginally used for providing a product and financial services efficiently. Although fintech is not a way to manually shift the use of financial implementation, because fintech has an objective to make it easier for users to receive products or loan funds. In relation to this it is necessary a clear arrangement of the establishment of the fintech companies themselves and it is regulated in the Financial Services Authority law in detail. It is necessary to provide legal protection for the users of fintech and economic actors themselves. The purpose of this research is to study the task of functions and the authority owned by the Financial Services Authority. The research method used with the type of normative research with secondary data source and primary, secondary and tertiary legal material is by reviewing the legislation relating to the Financial Services Authority Act . Opinions of legal experts and scientific articles relating to data analysis and data collection techniques in a deskritif by sorting through the relevant regulations. The arrangement and supervision of fintech must be done in accordance with the rules and provisions of course to anticipate the existence of a fintech that does not provide legal protection for its users, so in the rules of fintech is clearly regulated as well as the establishment of Digital financial innovation which volunteered as a supervisor under the roof of the Financial Services Authority institution as stipulated in the Financial Services Authority Act. It is necessary to socialize with fintech regulations for users.